2021
DOI: 10.1016/j.drugalcdep.2021.109100
|View full text |Cite
|
Sign up to set email alerts
|

Treatment provider perceptions of take-home methadone regulation before and during COVID-19

Abstract: Background The loosening of U.S. methadone regulations during the COVID-19 pandemic expanded calls for methadone reform. This study examines professional perceptions of methadone take-home dose regulation before and during the COVID-19 pandemic to understand responses to varied methadone distribution policies. Methods Fifty-nine substance use disorder treatment professionals were interviewed between 2017 and 2020 in-person or over video call. An inductive iterative codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…In a Canadian study, authors suggest that following the adoption of flexible protocols and expansion of take-home dosing, the reduction in directly observed dosing may have posed a risk to public safety, due to diversion of prescribed medication and its non-medical consumption [ 3 ]. In a US-based study, authors reported similar concerns from the side of OAT providers [ 48 ]. Respondents (OAT care providers) in that study also expressed concerns over the increased risk for overdose given that some clients might have consumed higher doses of OAT medication or use illicit drugs in combination.…”
Section: Discussionmentioning
confidence: 93%
“…In a Canadian study, authors suggest that following the adoption of flexible protocols and expansion of take-home dosing, the reduction in directly observed dosing may have posed a risk to public safety, due to diversion of prescribed medication and its non-medical consumption [ 3 ]. In a US-based study, authors reported similar concerns from the side of OAT providers [ 48 ]. Respondents (OAT care providers) in that study also expressed concerns over the increased risk for overdose given that some clients might have consumed higher doses of OAT medication or use illicit drugs in combination.…”
Section: Discussionmentioning
confidence: 93%
“…Current published research suggests a continuum of policy implementation by MOUD providers [18][19][20]. A study conducted in Texas and New Mexico among methadone treatment providers found varying perceptions about the benefits of multi-day take home dosing and concerns about provider liability and patient safety, including some who opposed them as threats to patient-centered care [21]. A Washington state OTP case study described provider concerns about blanket access to multi-day take home doses [13].…”
Section: Introductionmentioning
confidence: 99%
“…First, twenty out of 33 pilot participants received increased take-home dosing privileges, resulting in an estimated total of 113 fewer in-person dosing days in this sample, which potentially reduced COVID-19 transmission risk for patients and staff. Second, even with increased take-home doses, pilot participants on average had 53.15 out of 60 days with a methadone dose observed by a clinician (in-person or by video), which was markedly higher than matched controls who had 16.64 days with a methadone dose observed during the same period, suggesting that video observed dosing can increase assurance about methadone adherence, potentially help mitigate concerns about methadone poisonings or diversion, and help OTP providers obtain the assurance they often desire when increasing the number of take-home doses for some patients ( Madden et al, 2021 ). Third, the ability to observe methadone take-home dosing remotely often led to increased take-home privileges that could potentially reduce barriers that some patients experience with in-person requirements (e.g., limited transportation, childcare or employment obligations, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In response to the benefits of this blanket exception, SAMHSA extended this exception and will allow OTPs to offer increased take-home doses for up to one year after the expiration of the COVID-19 public health emergency ( Substance Abuse and Mental Health Services Administration, 2022b ). However, more frequent take-home dosing also imposes new challenges to OTP providers ( Hatch-Maillette et al, 2021 ), including potential concerns about risk for medication diversion, drug poisonings (i.e., overdose), and negative impacts on patient care and outcomes ( Madden et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%